Deformation of odd nuclei ²³Na, ²⁵Mg, and ²⁵Al in single-particle states - Korda, V.Yu.; Korda, L.P.; Klepikov, V.F.; Timchenko, I.S. (Problems of Atomic Science and Technology, 2023)
Using the evolutionary approach recently developed by us, the shapes of odd 2s1d-shell ²³Na, ²⁵Mg, and ²⁵Al nuc-lei in the ground and single-particle excited states have been extracted from the experimental data on the energies, spins, and parities of these states, as well as the measured probabilities of electromagnetic transitions between them. We have found that the single-particle spectra of the nuclei studied contain the single states and the continuous sets of states with abnormally weak deformation. This indicates the existence of the shape phase transitions from the spherical state of the nucleus into a deformed state. За допомогою розробленого нами нового еволюційного підходу форми непарних ядер 2s1d оболонки ²³Na, ²⁵Mg та ²⁵Al в основних та одночастинкових збуджених станах визначені з експериментальних даних про енергії, спіни та парності цих станів, а також виміряних ймовірностей електромагнітних переходів між ними. В одночастинкових спектрах досліджених ядер знайдені окремі стани та послідовності станів з аномально малою деформацією. Це свідчить про наявність фазових переходів із сферичного стану ядра в деформований стан.